2008
DOI: 10.1088/0022-3727/41/22/225201
|View full text |Cite
|
Sign up to set email alerts
|

New pathways for nanoparticle formation in acetylene dusty plasmas: a modelling investigation and comparison with experiments

Abstract: In this paper, the initial mechanisms of nanoparticle formation and growth in radiofrequency acetylene (C2H2) plasmas are investigated by means of a comprehensive self-consistent one-dimensional (1D) fluid model. This model is an extension of the 1D fluid model, developed earlier by De Bleecker et al. Based on the comparison of our previous results with available experimental data for acetylene plasmas in the literature, some new mechanisms for negative ion formation and growth are proposed. Possible routes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(120 citation statements)
references
References 69 publications
3
117
0
Order By: Relevance
“…Diacetylene is of interest for astronomy-it is a potential precursor for the H−C≡C−C≡C − anion, recently detected in interstellar space [1,2] and it was detected in the upper layers of planetary atmospheres (Titan, Uranus) [3,4], where free electrons also occur. Electron collisions with diacetylene are of interest also in technological plasmas [5,6]. Diacetylene is an important intermediate in flames [7,8], in particular, for the formation of soot [9].…”
Section: Introductionmentioning
confidence: 99%
“…Diacetylene is of interest for astronomy-it is a potential precursor for the H−C≡C−C≡C − anion, recently detected in interstellar space [1,2] and it was detected in the upper layers of planetary atmospheres (Titan, Uranus) [3,4], where free electrons also occur. Electron collisions with diacetylene are of interest also in technological plasmas [5,6]. Diacetylene is an important intermediate in flames [7,8], in particular, for the formation of soot [9].…”
Section: Introductionmentioning
confidence: 99%
“…Because the calculated densities of these species were fairly high, it was suggested that aromatic compounds might play a role as growth precursors for nanoparticles in hydrocarbon plasmas [47]. Another improvement of this model was presented by Ming et al [48]. Indeed, based on a comparison with experimental data, some new mechanisms for negative ion formation and growth, arising from dissociative electron attachment of (linear and branched) hydrocarbons (C 2n H 2 ), were proposed.…”
Section: Modeling Of Nanoparticle Formation In Plasmasmentioning
confidence: 99%
“…The dominance of the species with an even carbon atom number is a distinct feature of C 2 H 2 discharges. One-dimensional fluid simulations of capacitive C 2 H 2 plasmas have been performed for nanoparticle formation by De Bleecker et al [46] and Mao et al [47] in our group. The results showed that negative ions played a key role during the nanoparticle formation.…”
Section: The Plasma Chemistry For Cnt/cnf Growthmentioning
confidence: 99%
“…All data needed to calculate the diffusion coefficients of all the plasma species included in the models were adopted from [44] and [47]. For ions both motilities and diffusion coefficients are considered.…”
Section: Diffusion and Wall Deposition Lossesmentioning
confidence: 99%
See 1 more Smart Citation